SCIENTIFIC AND PEDAGOGICAL FOUNDATIONS OF METHODOLOGICAL APPROACHES TO PREPARING FUTURE PRIMARY SCHOOL TEACHERS FOR PROFESSIONAL ACTIVITY (European Journal of Interdisciplinary Research and Development, 2025)
This article discusses the scientific and pedagogical foundations of methodological approaches to the process of preparing future teachers of the subject of education for professional activity. In the modern educational system, the issues of forming the professional competence of the teacher, developing his methodological training, and effectively organizing the educational process are of great importance. The study analyzes the content of competence-based, systemic, activity-based, and personality-oriented approaches to the training of future teachers of educational science. The pedagogical possibilities of professional and methodological development are revealed based on the scientific views of world, CIS, and Uzbek pedagogical scientists.